Strongly \({g^{*}}\)-Closed Graph Function with Strongly-\({T_{i}{^{g^{*}}}}\) Spaces - Sivakumar, K.; Arunachalam, T.; Parimelazhagan, R. (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we introduce the graph function called Strongly \(g^{*}\)-closed graph function and studied some of their properties.